Spectrum and antibiotic sensitivity of bacterial keratitis: a retrospective analysis of eight years in a Tertiary Referral Hospital in Southwest China - Guo, Rui-Qin; Yang, Ji; Yang, Ya-Bin; Chen, Ya-Nan; Xiao, Yu-Yuan; Xiang, Ping; Dong, Meng-Jie; He, Min-Fang; Wang, Yin-Ting; Xiao, Yun-Ling; Ke, Hong-Qin; Liu, Hai (Frontiers in Cellular and Infection Microbiology, 2024)
Purpose The objective of this study was to investigate the epidemiological characteristics, distribution of isolates, prevailing patterns, and antibiotic susceptibility of bacterial keratitis (BK) in a Tertiary Referral Hospital located in Southwest China. Methods A retrospective analysis was conducted on 660 cases of bacterial keratitis occurring between January 2015 and December 2022. The demographic data, predisposing factors, microbial findings, and antibiotic sensitivity profiles were examined. Results Corneal trauma emerged as the most prevalent predisposing factor, accounting for 37.1% of cases. Among these cases, bacterial culture results were positive in 318 cases, 68 species of bacteria were identified. The most common Gram-Positive bacteria isolated overall was the staphylococcus epidermis and the most common Gram-Negative bacteria isolated was Pseudomonas aeruginosa. Methicillin-Resistant Staphylococci accounted for 18.1% of all Gram-Positive bacteria. The detection rate of P. aeruginosa showed an increasing trend over time (Rs=0.738, P=0.037). There was a significant decrease in the percentage of Gram-Negative microorganisms over time (Rs=0.743, P=0.035). The sensitivity of Gram-Positive bacteria to linezolid, vancomycin, tigecycline, quinupristin/dalfopristin, and rifampicin was over 98%. The sensitivity rates of Gram-Negative bacteria to amikacin, meropenem, piperacillin/tazobactam, cefoperazone sodium/sulbactam, ceftazidime, and cefepime were all above 85%. In patients with a history of vegetative trauma, the possibility of BK should be taken into account in addition to the focus on fungal keratitis. Conclusion The microbial composition primarily consists of Gram-Positive cocci and Gram-Negative bacilli. Among the Gram-Positive bacteria, S. epidermidis and Streptococcus pneumoniae are the most frequently encountered, while P. aeruginosa is the predominant Gram-Negative bacteria. To combat Gram-Positive bacteria, vancomycin, linezolid, and rifampicin are considered excellent antimicrobial agents. When targeting Gram-Negative pathogens, third-generation cephalosporins exhibit superior sensitivity compared to first and second-generation counterparts. As an initial empirical treatment for severe cases of bacterial keratitis and those unresponsive to fourth-generation fluoroquinolones in community settings, the combination therapy of vancomycin and tobramycin is a justifiable approach. Bacterial keratitis can be better managed by understanding the local etiology and antibacterial drug susceptibility patterns.